Testing of the Function Focused Environment Assessment and the Function Focused Policy Assessment in Assisted Living. Issue 2 (3rd April 2019) - Resnick, Barbara; Galik, Elizabeth; Boltz, Marie; Vigne, Erin; Holmes, Sarah; Fix, Steven; Zhu, Shijun; Lewis, Regina
Abstract: This study tested two new instruments, the Function Focused Environment Assessment (FF-EA) and the Function Focused Policy Assessment (FF-PA). The measures were developed for clinical evaluation of assisted living (AL) settings to help optimize function and physical activity among residents. In total, 106 AL settings and 242 residents were included. There was evidence of item reliability (0.92) and interrater reliability (kappa =0.40, p = .015; agreement 85%) of FF-EA and item reliability (0.89) and interrater reliability (kappa =0.48, p = .001, agreement 82%) of the FF-PA, and support for validity of both measures based on INFIT and OUTFIT statistics and hypothesis testing.